Pendampingan Anak Migran dalam Pembelajaran Al-Qur’an Melalui Strategi Menyanyi dan Mendongeng di PKBM PNF KBRI Kuala Lumpur Malaysia : Penelitian - Siti Luluk Nafisah; Qurroti A’yun; Moch. Mahsun; Nurhafid Ishari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
At the Indonesian Embassy's Non-Formal Learning Center (PKBM PNF) in Kuala Lumpur, writing and reading strategies are commonly used as classroom learning methods, but some students complained that they felt uncomfortable with this learning model. The use of singing and storytelling strategies was chosen because they were considered to have the potential to increase students' interest in learning, strengthen memorization, and deepen their appreciation of religious attitudes. This mentoring used the service learning method and was designed specifically for students at the Indonesian Embassy's Non-Formal Learning Center (PKBM PNF) in Kuala Lumpur. Data were collected through interviews, observations, and memorization and comprehension tests before and after the intervention. The mentoring results showed that students' memorization and comprehension abilities increased significantly after the singing and storytelling learning strategies. In addition, this method successfully accelerated material mastery and created a more enjoyable and interactive learning environment. This study suggests the use of singing and storytelling as creative and enjoyable learning methods, especially for students who have difficulty memorizing and understanding the Quran.